Separator for electrochemical device, electrochemical device including the same, and method for manufacturing the same
By introducing binder resin, inorganic particles and elastomers into the separator of lithium secondary batteries, the problems of shrinkage and insufficient impact resistance of the separator at high temperatures are solved, the high thermal stability and impact resistance of the separator are achieved, and the Overall battery performance.
Patent Information
- Application Number
- CN202080067210.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-18
- Filing Date
- 2020-10-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-10-16
AI Technical Summary
The porous polymer diaphragms of existing lithium secondary batteries will shrink or melt at high temperatures, resulting in low heat resistance, and the self-standing diaphragms are easily damaged under external impact, and the size changes and interface resistance increase, affecting battery performance.
By introducing binder resin and inorganic particles into the separator, and adding elastomers, the elongation of the separator is increased and dimensional changes are reduced.
It achieves high thermal stability and impact resistance of the separator, reduces dimensional changes and interface resistance, and improves the overall performance of the battery.
Smart Images

Figure CN114514654B_ABST
Abstract
Description
Technical Field
[0001] This application claims the priority of Korean Patent Application No. 10-2019-0130071 filed in Korea on October 18, 2019. The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the separator. The present disclosure also relates to a method for manufacturing a separator. Background Art
[0002] Recently, in the field of electrochemical devices, the guarantee of safety has received more and more attention. In particular, secondary batteries, such as lithium secondary batteries, include an electrode assembly including a positive electrode, a negative electrode and a separator, and the electrode assembly can be manufactured so that it can have a structure in which the separator is placed between the positive electrode and the negative electrode. A porous film using a polyolefin polymer resin has been used as a separator substrate for such a lithium secondary battery. However, such a porous polymer film shrinks or melts at high temperatures, resulting in a problem of low heat resistance. In order to solve this problem, a porous polymer film coated with an inorganic particle coating on the surface, or a self-supporting separator containing only an inorganic material and a binder resin without a polymer separator substrate has been proposed. When an inorganic material is applied to a separator as described above, thermal shrinkage and safety can be improved. However, the resulting separator may experience an increase in thickness and dimensional changes in width and length due to its volume expansion, resulting in a defect in the appearance of the battery. In addition, the separation of the separator from the electrode will generate bubbles in the battery, the interface resistance between the electrode and the separator increases, and lithium may be deposited in the gap between the electrode and the separator, resulting in a problem of increased battery resistance. Therefore, it is necessary to reduce the dimensional change of the self-standing diaphragm. In addition, it is necessary to increase the elongation of the self-standing diaphragm because the self-standing diaphragm is easily damaged by external impact. Summary of the invention
[0003] [Technical issues]
[0004] The present disclosure is intended to solve the problems of the related art, and therefore the present disclosure is intended to provide a self-supporting diaphragm including a binder resin and inorganic particles. In particular, the present disclosure also relates to a diaphragm with improved elongation and reduced dimensional change by introducing an elastomer into a binder resin. In addition, the present disclosure is intended to provide a diaphragm having the above-mentioned structural features. In addition, the present disclosure is intended to provide an electrochemical device comprising a positive electrode, a negative electrode, a diaphragm disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the diaphragm is the above-mentioned diaphragm. These and other objects and advantages of the present disclosure can be understood from the following detailed description and will become more apparent from the exemplary embodiments of the present disclosure. In addition, it is easily understood that the objects and advantages of the present disclosure can be achieved by the means and combinations thereof shown in the appended claims.
[0005] [Technical solution]
[0006] According to a first embodiment of the present disclosure, an insulating porous layer for an electrochemical device separator is provided, which includes inorganic particles and a binder resin, wherein the inorganic particles are present in the insulating porous layer in a proportion of 70-95 wt % based on 100 wt % of the insulating porous layer, and the binder resin includes an elastomer.
[0007] According to a second embodiment of the present disclosure, there is provided the insulating porous layer as defined in the first embodiment, wherein the elastomer is present in an amount of 5 to 50 wt % based on 100 wt % of the binder resin.
[0008] According to a third embodiment of the present disclosure, there is provided the insulating porous layer as defined in the second embodiment, wherein the elastomer is present in an amount of 5 to 25 wt % based on 100 wt % of the binder resin.
[0009] According to a fourth embodiment of the present disclosure, an insulating porous layer as defined in any one of the first to third embodiments is provided, wherein the elastomer includes at least one selected from the following group: natural rubber, nitrile rubber, acrylonitrile butadiene rubber, styrene butadiene rubber, chloroprene rubber, butadiene rubber, ethylene propylene diene rubber, olefin thermoplastic elastomer, urethane thermoplastic elastomer, styrene block copolymer, thermoplastic polyester elastomer, thermoplastic copolyester, thermoplastic copolyamide, acrylated styrene butadiene rubber, etc.
[0010] According to a fifth embodiment of the present invention, there is provided an insulating porous layer as defined in any one of the first to fourth embodiments, wherein the molecular weight (Mw) of the elastomer is 10,000-1,000,000 g / mol.
[0011] According to a sixth embodiment of the present invention, there is provided the insulating porous layer as defined in the fifth embodiment, wherein the molecular weight (Mw) of the elastomer is 200,000-700,000 g / mol.
[0012] According to a seventh embodiment of the present invention, there is provided an insulating porous layer as defined in any one of the first to sixth embodiments, wherein the inorganic particles include Al 2 O 3 、AlOOH、Al(OH) 3 、AlN、BN、MgO、Mg(OH) 2 、SiO 2 , ZnO, TiO 2 、BaTiO 3 or a mixture thereof.
[0013] According to an eighth embodiment of the present invention, there is provided the insulating porous layer as defined in any one of the first to seventh embodiments, wherein the average particle diameter of the inorganic particles is 0.001 to 3 μm.
[0014] According to a ninth embodiment of the present invention, there is provided the insulating porous layer as described in any one of the first to eighth embodiments, which has a thickness of 0.01 to 50 μm.
[0015] According to a tenth embodiment of the present disclosure, there is provided a separator for an electrochemical device including only the insulating porous layer as defined in any one of the first to ninth embodiments.
[0016] According to an eleventh embodiment of the present invention, there is provided an electrochemical device including a negative electrode, a positive electrode, and a separator disposed between the negative electrode and the positive electrode, wherein the separator is an insulating porous layer defined in any one of the first to ninth embodiments.
[0017] [Beneficial Effects]
[0018] The diaphragm of the embodiment of the present disclosure mainly includes inorganic particles and a binder resin, which can be used as a self-supporting diaphragm without a diaphragm substrate (such as a polymer resin film) and does not cause thermal shrinkage problems. In addition, the diaphragm of the embodiment of the present disclosure shows a smaller dimensional change and a higher elongation due to the introduction of an elastomer, and is prevented from being damaged by external impact.
[0019] Description of the drawings
[0020] The accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the foregoing disclosure, are used to provide a further understanding of the technical features of the present disclosure. Therefore, the present disclosure is not interpreted as being limited to the accompanying drawings.
[0021] Figure 1 Graph showing the elongation of each separator of Example 1, Example 2, and Comparative Example 1.
[0022] Figure 2 Graph showing the resistance of each separator of Example 1, Example 2, and Comparative Example 1.
[0023] Figure 3 Graphs illustrating dimensional changes of each separator of Example 1, Example 2, and Comparative Example 1.
[0024] Figure 4 and Figure 5 Photographs illustrating the negative electrode-separator stack products of Example 3 and Example 4, respectively, after impregnation with electrolyte are shown.
[0025] Figure 6 A photograph illustrating the negative electrode-separator laminate product of Comparative Example 2 after impregnation with an electrolyte is shown. DETAILED DESCRIPTION
[0026] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before the description, it should be understood that the terms used in the specification and the appended claims should not be interpreted as limited to the general and dictionary meanings, but are interpreted based on the meanings and concepts corresponding to the technical aspects of the present disclosure based on the principle of allowing the inventor to appropriately define the terms to obtain the best interpretation. Therefore, the description presented herein is only a preferred embodiment for illustrative purposes and is not intended to limit the scope of the present invention, so it should be understood that other equivalent substitutions and modifications may be made thereto without departing from the scope of the present disclosure.
[0027] The terms used in the specification are for illustrative purposes only and are intended to describe exemplary embodiments, but the scope of the present disclosure is not limited thereto. As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0028] In addition, it should be understood that when used in this specification, the terms "including", "having" or "comprising" refer to the existence of any specified shapes, numbers, steps, operations, parts, elements and / or groups, but do not exclude the addition of one or more other shapes, numbers, steps, operations, parts, elements and / or their groups.
[0029] In one aspect of the present disclosure, an insulating porous layer is provided. The insulating porous layer can be used as a separator of an electrochemical device. In this article, a typical example of an electrochemical device may be a rechargeable secondary battery including a unit cell formed by stacking a positive electrode, a separator, and a negative electrode in sequence.
[0030] In another aspect of the present disclosure, a diaphragm for an electrochemical device comprising the insulating porous layer is provided, in particular a self-supporting diaphragm comprising only the insulating porous layer. According to the present disclosure, the self-supporting diaphragm is a diaphragm comprising only the insulating porous layer and not including any other elements (e.g., a diaphragm substrate, such as a polymer resin film) other than the insulating porous layer of the present disclosure.
[0031] According to one embodiment of the present disclosure, the insulating porous layer is an organic / inorganic composite film including inorganic particles and a binder resin. In the insulating porous layer, the inorganic particles are bound to each other by the binder resin so that they can be stacked in a layered structure. According to the present disclosure, the organic / inorganic composite film has a porous characteristic of pores formed by the interstitial volume between the inorganic particles. The interstitial volume refers to the space defined by the inorganic particles that are substantially facing each other in the stacking structure of the inorganic particles. The pores are interconnected so that a gas or liquid can pass from one surface of the substrate through the substrate to the other surface thereof.
[0032] According to an embodiment of the present disclosure, there is no particular limitation on the inorganic particles, as long as they are electrochemically stable and have a particle size that is compatible with the thickness of the insulating porous layer. In other words, there is no particular limitation on the inorganic particles used according to the present disclosure, as long as they are within the operating voltage range of the applicable battery (e.g., based on Li / Li + The inorganic particles may have a particle size of 0.001-3 μm or 0.001-2 μm. When the size of the inorganic particles is less than 0.001 μm, the dispersibility may be reduced. When the size of the inorganic particles is greater than 3 μm, it is difficult to provide the resulting insulating porous layer in the form of a film. Therefore, when the insulating porous layer is applied alone to the diaphragm, the diaphragm exhibits an excessively large pore size, resulting in deterioration of the insulating properties. In view of the above, the inorganic particles may be controlled to have a particle size of about 20-500 nm.
[0033] Non-limiting examples of inorganic particles include Al 2 O 3 、AlOOH、Al(OH) 3 、AlN、BN、MgO、Mg(OH) 2 、SiO 2 , ZnO, TiO 2 、BaTiO 3 or a mixture thereof. The insulating porous layer may include at least one of the above-listed inorganic particles.
[0034] Based on 100 wt % of the insulating porous layer, the insulating porous layer may include 70-95 wt % of inorganic particles. For example, within the above-defined range, the content of the inorganic particles may be 90 wt % or less. When the content of the inorganic particles is too high, the content of the binder resin is reduced, so the inorganic particles may be easily detached from the insulating porous layer, and the insulating porous layer may exhibit low durability, including brittleness. On the contrary, when the content of the inorganic particles is too low, the proportion of the binder resin increases and the insulating porous layer shows low porosity, resulting in deterioration of the resistance characteristics.
[0035] In addition, the binder resin provides adhesion and insulation for the inorganic particles, and imparts adhesion between the porous layer and the electrode. According to the present disclosure, the binder resin includes an elastomer. According to the present disclosure, an elastomer refers to a material having an elasticity that can be stretched to more than twice its original length under stress and then can be rapidly contracted to its original length when relaxed. Based on 100% by weight of the binder resin, the binder resin may include an elastomer in an amount of 5-50% by weight or 5-25% by weight. When the content of the elastomer is less than 5% by weight, the effect of the elastomer can not be fully provided. On the other hand, when the content of the elastomer is greater than 50% by weight, the slurry prepared by mixing the elastomer with another binder resin (e.g., a polyvinylidene fluoride binder resin) may show an undesirable unstable phase. In particular, the elastomer may include at least one selected from the group consisting of natural rubber, nitrile rubber, acrylonitrile butadiene rubber, styrene butadiene rubber, chloroprene rubber, butadiene rubber, ethylene propylene diene rubber, olefin thermoplastic elastomers, urethane thermoplastic elastomers, styrene block copolymers, thermoplastic polyester elastomers, thermoplastic copolyesters, thermoplastic copolyamides, acrylated styrene butadiene rubber, etc. According to an embodiment of the present disclosure, the elastomer may be an elastomer that is soluble in a solvent and has a molecular weight (Mw) of 10,000-1,000,000 g / mol or 200,000-700,000 g / mol. According to an embodiment of the present disclosure, the molecular weight may be determined by gel permeation chromatography (GPC).
[0036] Meanwhile, if necessary, in addition to the elastomer, the binder resin may also include any one selected from the following group: polyvinylidene fluoride (PVdF)-based resin, styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyethylene glycol (PEG), polypropylene glycol (PPG), toluene diisocyanate (TDI), polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, poly(ethylene-co-vinyl acetate), polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer and polyimide, or a mixture of two or more thereof.
[0037] The thickness of the insulating porous layer is not particular. For example, the insulating porous layer may have a thickness of 0.01 to 50 μm.
[0038] In addition, the insulating porous layer is not particularly limited in terms of its pore size and porosity. Preferably, the insulating porous layer may have a pore size of 0.001-3 μm or 0.001-2 μm and a porosity of 10-90% by volume. The pore size and porosity depend largely on the size of the inorganic particles, but may be affected by the type of binder resin. For example, when inorganic particles with a particle size of 1 μm or less are used, the pore size may be about 1 μm or less. This pore structure is filled with an electrolyte subsequently injected, and the electrolyte acts as a conductive ion. When the pore size and porosity are less than 0.001 μm and less than 10% by volume, respectively, the resulting insulating porous layer may act as a resistive layer. When the pore size and porosity are greater than 10 μm and greater than 90% by volume, respectively, the resulting insulating porous layer may exhibit reduced mechanical properties.
[0039] Meanwhile, according to the present disclosure, the porosity and pore size may be determined using BELSORP (BET system) available from BEL JAPAN Co. with an adsorbed gas (e.g., nitrogen), or using a mercury intrusion porosimetry method, capillary flow porosimetry, etc. According to an embodiment of the present disclosure, the porosity may be calculated from the thickness and weight of the resulting coating and the theoretical density of the coating.
[0040] According to an embodiment of the present disclosure, the insulating porous layer may be obtained by preparing a composition for forming an insulating porous layer including inorganic particles and a binder resin, and forming the composition into a sheet-shaped film.
[0041] First, the composition for forming an insulating porous layer can be obtained as follows: a polymer solution containing a binder resin dissolved in a solvent and a dispersion containing inorganic particles dispersed in a solvent are prepared separately, and the polymer solution is mixed with the dispersion. The inorganic particles can be added after being crushed to a predetermined average particle size. Alternatively, the inorganic particles are added to a solvent and then dispersed in the solvent, while being controlled to have a predetermined particle size using a ball milling process, etc., to provide a dispersion. At the same time, according to an embodiment of the present disclosure, the content of solids other than the solvent in the polymer solution can be controlled to be less than 10% by weight, for example, 5-7% by weight. When the solid content is greater than 10% by weight, the binder may not be fully dissolved in the solvent. In addition, it is preferred that the content of solids other than the solvent in the dispersion be controlled to be 30-70% by weight.
[0042] The polymer solution and the dispersion can be mixed using a mixing device such as a homodiper. For example, when a homodiper is used to prepare the composition, mixing can be performed at about 2000 rpm for about 30 minutes.
[0043] Then, the composition is applied to the release sheet and dried to form an insulating porous layer. The composition can be applied by a coating method appropriately selected from known coating methods, including dip coating, slit coating, micro gravure coating, line coating and blade coating. In particular, slit coating or dip coating is preferably used. The slit coating method includes applying the composition supplied by the slit die to the entire surface of the release sheet, and the thickness of the applied composition can be controlled according to the flux supplied by the metering pump. In addition, the dip coating method includes immersing the release sheet in a tank containing the composition for coating, and the thickness of the applied composition can be controlled according to the concentration of the composition and the speed of removing the release sheet from the composition tank.
[0044] Meanwhile, the release sheet is not particularly limited as long as the resulting insulating porous layer is not damaged when it is removed. For example, the release sheet may include a glass plate or a polymer film made of polyethylene terephthalate.
[0045] The solvent for the composition preferably has a solubility parameter and a low boiling point similar to the solubility of the binder resin to be used, so as to promote the removal of the organic solvent during the drying process. This is because such a solvent is conducive to uniform mixing and subsequent removal. In view of the above, the solvent preferably has a boiling point of 80-180°C or 100-165°C. Non-limiting examples of solvents include acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, mesitylene, dimethylacetamide, dimethyl sulfone, dimethyl carbonate, methyl ethyl ketone, methyl acetate, cyclohexanone, etc. The above solvents can be used alone or in combination. Preferably, the solvent may include any one selected from N-methyl-2-pyrrolidone (NMP), cyclohexane, mesitylene, dimethylacetamide, dimethyl sulfone and dimethyl carbonate or a mixture of two or more thereof.
[0046] Then, the composition is dried to remove the solvent and obtain a sheet-like insulating porous layer. The composition can be dried naturally or heated. Heating can generally be carried out by heating processes such as heaters, ovens, resistance heating, electric induction heating, hot air heating, infrared heating, etc. The release sheet can be used not only as a carrier for coating the slurry thereon, but also as a component for drying the slurry and removing the organic solvent. Therefore, after providing a heating device for the release sheet, heating can also be carried out by heating the release sheet. The heating can be carried out at a temperature of about 40°C-200°C, preferably about 60°C-180°C. In addition, the heating time is not particularly limited and can be about 10 minutes to 2 hours. After the composition is completely dried, the release sheet is removed to obtain the insulating porous layer.
[0047] In another aspect, an electrochemical device comprising a separator of the present disclosure is provided. The electrochemical device comprises a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the above-mentioned insulating porous layer of an embodiment of the present disclosure. In one variation, the separator may be a composite separator comprising an insulating porous layer laminated with a porous polymer film.
[0048] Electrochemical devices include any device that performs an electrochemical reaction, and specific examples thereof include all types of primary batteries, secondary batteries, fuel cells, solar cells or capacitors, such as supercapacitor devices. In particular, among secondary batteries, lithium secondary batteries are preferred, including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries or lithium ion polymer batteries.
[0049] According to the present disclosure, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the current collector and containing a positive electrode active material, a conductive material and a binder resin. The positive electrode active material may include any one selected from the following: a layered compound, such as a lithium manganese composite oxide (LiMn 2 O 4 、LiMnO 2 etc.), lithium cobalt oxide (LiCoO 2 ) and lithium nickel oxide (LiNiO 2 ), or those compounds substituted by one or more transition metals; lithium manganese oxides, such as those of the formula Li 1+x Mn 2-x O 4 (where x is 0-0.33), LiMnO 3 、LiMn 2 O 3 and LiMnO 2 Those represented by; lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 ,LiV 3 O 4 、V 2 O 5 or Cu 2 V 2 O 7 ; With chemical formula LiNi 1-x M x O 2 Ni-type lithium nickel oxide represented by the chemical formula LiMn 1-x M x O 2(where M = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 - 0.1) or Li 2 Mn 3 MO 8 a lithium manganese composite oxide represented by (where M = Fe, Co, Ni, Cu or zinc); LiMn in which Li is partially substituted by alkaline earth metal ions 2 O 4 ; a disulfide compound; and Fe 2 (MoO 4 ) 3 ; or a mixture of two or more of them.
[0050] According to the present disclosure, the negative electrode includes a negative electrode current collector and a negative electrode active material layer formed on at least one surface of the current collector and containing a negative electrode active material, a conductive material, and a binder resin. The negative electrode may include any one selected from the following as the negative electrode active material: a lithium metal oxide; carbon, such as non-graphitized carbon or graphitic carbon; a metal composite oxide, such as Li x Fe 2 O 3 (0 ≤ x ≤ 1), Li x WO 2 (0 ≤ x ≤ 1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, an element of Group 1, 2 or 3 in the periodic table, a halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); a lithium metal; a lithium alloy; a silicon-based alloy; a tin-based alloy; a metal oxide, such as SnO, SnO 2 , PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 and Bi 2 O 5 ; a conductive polymer, such as polyacetylene; a Li-Co-Ni type material; and titanium oxide; or a mixture of two or more of them.
[0051] According to one embodiment of the present disclosure, the conductive material may be any one selected from the group consisting of graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon and polyphenylene derivatives, or a mixture of two or more such conductive materials. More specifically, the conductive material may be any one selected from the group consisting of natural graphite, artificial graphite, Super-P, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate and titanium dioxide, or a mixture of two or more such conductive materials.
[0052] The current collector is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has high conductivity. Specific examples of the current collector may include stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver, etc.
[0053] The binder resin can be a polymer currently used in the art for electrodes. Non-limiting examples of binder resins include, but are not limited to: poly(vinylidene fluoride-co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, poly(ethylene-co-vinyl acetate), polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose.
[0054] The electrode assembly prepared as described above may be introduced into a suitable case and an electrolyte may be injected therein to obtain a battery.
[0055] According to the present invention, the electrolyte is A + B - A salt of the structure + Including alkali metal cations such as Li + 、Na + , K + or a combination thereof, B - Including anions such as PF 6 - , BF 4 - , Cl - Br - ,I - , ClO 4 - , AsF 6 - , CH 3 CO 2 - CF 3SO 3 - 、N(CF 3 SO 2 ) 2 - , C(CF 2 SO 2 ) 3 - Or a combination thereof, the salt is dissolved or dissociated in an organic solvent selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma-butyrolactone (g-butyrolactone), ester compounds, and mixtures thereof. However, the present disclosure is not limited thereto.
[0056] In addition, the present disclosure provides a battery module, which includes a battery including the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to: an electric tool driven by the power of an electric motor; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc.; an electric two-wheeled vehicle, including an electric bicycle and an electric scooter; an electric golf cart; a power storage system; etc.
[0057] The following will be described more completely in order to easily understand the present disclosure. However, the following embodiments may be embodied in many different forms and should not be construed as being limited to the exemplary embodiments set forth herein. On the contrary, these exemplary embodiments are provided to make the present disclosure thorough and complete and to fully convey the scope of the present disclosure to those skilled in the art.
[0058] Example 1
[0059] Nitrile rubber (NBR, Mw: 600,000 g / mol) was dissolved in N-methylpyrrolidone (NMP) to prepare a polymer solution (first solution) having a solid content of 5 wt%. In addition, PVdF was dissolved in NMP to prepare a polymer solution (second solution), wherein the molecular weight (Mw) of PVdF was 1,400,000 g / mol and the solid content of the polymer solution was 6 wt%. Then, AlOOH (particle size D 50: 40nm) is introduced into NMP and dispersed therein using a ball mill to prepare a dispersion (solid content 50 weight %). Ball milling is carried out for 3 hours with a bead size of 0.5cm. Afterwards, the first polymer solution, the second polymer solution and the dispersion are mixed with a homodiper to prepare a composition for an insulating porous layer. Mixing is carried out for about 30 minutes at a rate of about 2000rpm. In the composition for the insulating porous layer, the weight ratio of the content of the binder resin to the content of the inorganic particles is about 20:80. In addition, the weight ratio of NBR and PVdF is 21:79. The resulting composition is coated on a glass plate to a thickness of 400μm using a rod coater device.
[0060] The glass plate coated with the composition was introduced into a convection oven and dried at 150° C. for 30 minutes, and then the glass plate was removed to obtain an insulating porous layer. The obtained insulating porous layer was cut into a size of 8 cm×10 cm (width×length).
[0061] Example 2
[0062] An insulating porous layer was prepared in the same manner as in Example 1, except that hydrogenated NBR (H-NBR) (Mw: 600,000 g / mol) was used as the binder resin instead of NBR.
[0063] Comparative Example 1
[0064] An insulating porous layer was prepared in the same manner as in Example 1, except that PVdF (Mw: 1,400,000 g / mol) was used as a binder resin in the total amount of the binder.
[0065] Manufacturing Example: Method for Manufacturing Negative Electrode
[0066] First, 97.6 parts by weight of graphite as a negative electrode active material, 1.2 parts by weight of styrene-butadiene rubber (SBR) as a binder, and 1.2 parts by weight of carboxymethyl cellulose (CMC) were mixed to prepare a negative electrode mixture. Then, the negative electrode mixture was dispersed in ion exchange water to prepare a negative electrode slurry. The slurry was coated on both sides of a copper foil with a thickness of 20 μm, and then dried and pressed to obtain a negative electrode.
[0067] Example 3
[0068] The insulating porous layer of Example 1 was stacked with the negative electrode prepared as described in the above-mentioned Manufacturing Example, and lamination was performed at 100° C. and 6.5 MPa to obtain a laminated structure.
[0069] Example 4
[0070] The insulating porous layer of Example 2 was stacked with the negative electrode prepared as described in the above-mentioned Manufacturing Example, and lamination was performed at 100° C. and 6.5 MPa to obtain a laminated structure.
[0071] Comparative Example 2
[0072] The insulating porous layer of Comparative Example 1 was stacked with the negative electrode prepared as described in the above Manufacturing Example, and lamination was performed at 100° C. and 6.5 MPa to obtain a laminated structure.
[0073] Determination of elongation
[0074] For each example and comparative example, each insulating porous layer of the example and comparative example was prepared into 6 pieces of 100 mm×20 mm size. Each piece was stretched at a speed of 500 mm / min using an Instron instrument at room temperature to determine the elongation at break. The elongation is expressed as the average value of six pieces of each insulating porous layer. Here, the sample area for measurement was 20 mm×20 mm.
[0075] refer to Figure 1 , compared with Comparative Example 1, the insulating porous layers of Examples 1 and 2 show higher elongation.
[0076] Evaluation of electrolyte immersion (1)
[0077] Each of the insulating porous layers of Examples 1 and 2 and Comparative Example 1 was cut into a size of 15 cm×15 cm to prepare a sample. Ethylene carbonate / ethylmethyl carbonate / dimethyl carbonate was mixed at a volume ratio of 3:3:4, and 1.0 M LiPF 6 To prepare the electrolyte. Each insulating porous layer sample was immersed in 10 mL of the electrolyte for 10 minutes, and then the changes in the width and length of each insulating porous layer were measured to calculate the dimensional change. The results are shown as average values. Reference Figure 3 , Comparative Example 1 shows a 2.4% increase in length compared to the initial length of the insulating porous layer. In contrast, Example 1 and Example 2 show increases in length of 2.1% and 2.3%, respectively. Therefore, it can be seen that Examples 1 and 2 show a lower size increase compared to Comparative Example 1.
[0078] Evaluation of electrolyte immersion (2)
[0079] Each of the stacked structures of Examples 3 and 4 and Comparative Example 2 was cut into a size of 15 cm×15 cm to prepare a sample. Ethylene carbonate / ethylmethyl carbonate / dimethyl carbonate were mixed at a volume ratio of 3:3:4, and 1.0 M LiPF 6 Each sample was immersed in 10 mL of the electrolyte for 1 day, and the appearance of each stacked structure was examined. Figure 4 and Figure 5are photographs respectively illustrating the appearance of Example 3 and Example 4. It can be seen that the dimensional change of the insulating porous layer is small, so the laminated structure maintains its smooth surface. Figure 6 is a photograph illustrating the appearance of the laminated structure of Comparative Example 2. It can be seen that the insulating porous layer of Comparative Example 2 undergoes dimensional changes, resulting in deformation of its appearance.
[0080] Resistance measurement
[0081] The resistance of each insulating porous layer sample of the embodiment and the comparative example was determined as follows. 6 Dissolved in a mixed solvent containing ethylene carbonate, propylene carbonate and propyl propionate in a volume ratio of 25:10:65 to a concentration of 1 M to prepare an electrolyte. Each insulating porous layer sample was impregnated with the electrolyte, and the resistance was measured using a multi-probe analyzer (Hioki Co.). Figure 2 It can be seen that the insulating porous layer samples of Examples 1 and 2 show lower resistance than the insulating porous layer sample of Comparative Example 1. Figure 2 , it can be seen that, compared with the insulating porous layer of Comparative Example 1, the insulating porous layers of Examples 1 and 2 show lower resistance.
Claims
1. An electrochemical device comprising a negative electrode, a positive electrode and a separator disposed between the negative electrode and the positive electrode, wherein: The separator is an insulating porous layer comprising inorganic particles and a binder resin, wherein the ratio of the inorganic particles in the insulating porous layer is 70 wt % to 95 wt % based on 100 wt % of the insulating porous layer, and the binder resin comprises an elastomer; wherein the diaphragm is a self-supporting diaphragm without a diaphragm substrate; wherein, based on 100 wt % of the binder resin, the elastomer is present in an amount of 5 wt % to 50 wt %, and the molecular weight (Mw) of the elastomer is 200000 to 700000 g / mol; Wherein, the elastomer comprises hydrogenated nitrile rubber.
2. The electrochemical device according to claim 1, wherein The elastomer may be present in an amount of 5 wt % to 25 wt % based on 100 wt % of the binder resin.
3. The electrochemical device according to claim 1, wherein The elastomer also includes at least one selected from the following groups: natural rubber, nitrile rubber, acrylonitrile butadiene rubber, styrene butadiene rubber, chloroprene rubber, butadiene rubber, ethylene propylene diene rubber, olefin thermoplastic elastomer, urethane thermoplastic elastomer, styrene block copolymer, thermoplastic polyester elastomer, thermoplastic copolyester, thermoplastic copolyamide, acrylated styrene butadiene rubber.
4. The electrochemical device according to claim 1, wherein The inorganic particles include Al2O3, AlOOH, Al(OH)3, AlN, BN, MgO, Mg(OH)2, SiO2, ZnO, TiO2, BaTiO3 or a mixture thereof.
5. The electrochemical device according to claim 1, wherein The average particle size of the inorganic particles is 0.001-3 μm.
6. The electrochemical device according to claim 1, wherein The thickness of the insulating porous layer is 0.01-50 μm.
Citation Information
Patent Citations
Double coated tape exhibiting improved reworkable capability
KR1020190130071A
Separator for nonaqueous secondary batteries, and nonaqueous secondary battery
CN105051940A
Stacked body, separator for non-aqueous electrolyte secondary batteries which includes stacked body, and non-aqueous electrolyte secondary battery
CN105706270A
Method for manufacturing separator, separator manufactured therefrom, and electrochemical element comprising same
CN105814711A
Separator and electrochemical device comprising same
CN108370015A